Nationaliteit in Belgisch Congo: constructie en verbeelding - De Meester, Tom (Afrika Focus, 1998)
This article discusses nationality law in the Belgian Congo and analyses theoretical disputes in the contemporary legal literature concerning issues of nationality and racial segregation in colonial society. The Belgian nationality of the black inhabitants of the Congo region is depicted as mere rhetoric, since it did not protect them from racial segregation and severe discrimination. The minor importance of national boundaries in colonial society and the domination of social reality by a hegemonic racial idiom were reflected in an insufficient and inaccurate nationality law. Colonial law and regulations moreover, were built around racial categories the mutual boundaries of which were not clearly defined. KEY WORDS : Congo, colonial law, nationality law, racial domination, colonial discourse